An elastic/viscoelastic finite element analysis method for crustal deformation using a 3-D island-scale high-fidelity model. Issue 1 (4th April 2016) - Ichimura, Tsuyoshi; Agata, Ryoichiro; Hori, Takane; Hirahara, Kazuro; Hashimoto, Chihiro; Hori, Muneo; Fukahata, Yukitoshi
Abstract: As a result of the accumulation of high-resolution observation data, 3-D high-fidelity crustal structure data for large domains are becoming available. However, it has been difficult to use such data to perform elastic/viscoelastic crustal deformation analyses in large domains with quality assurance of the numerical simulation that guarantees convergence of the numerical solution with respect to the discretization size because the costs of analysis are significantly high. This paper proposes a method of constructing a high-fidelity crustal structure finite element (FE) model using high-fidelity crustal structure data and fast FE analysis to reduce the costs of analysis (based on automatic FE model generation for parallel computation, OpenMP/MPI hybrid parallel computation on distributed memory computers, a geometric multigrid, variable preconditioning and multiple precision arithmetic). Using the proposed methods, we construct 10 billion degree-of-freedom high-fidelity crustal structure FE models for the entire Japan, and conduct elastic/viscoelastic crustal deformation analysis using this model with enough high accuracy of the numerical simulation.